Robotic distal gastrectomy plus spleen-preserving distal pancreatectomy: optimal resection for simultaneous gastric cancer and intraductal papillary mucinous neoplasm of the pancreatic body - Sunao Ito; Hiroyuki Sagawa; Kohei Fujita; Masaki Saito; Shinnosuke Harata; Shunsuke Hayakawa; Kenta Saito; Tatsuya Tanaka; Mamoru Morimoto; Ryo Ogawa; Hiroki Takahashi; Yoichi Matsuo; et al. (Surgical Case Reports)
Abstract Background Organ-preserving surgery has recently gained increasing attention. However, performing the surgery for duplicated gastric and distal pancreatic tumors is difficult because of procedural complexity and concerns of remnant gastric necrosis. We present the first case of simultaneous robotic distal gastrectomy plus spleen-preserving distal pancreatectomy in a patient with overlapping gastric cancer and intraductal papillary mucinous neoplasm. Case presentation A 78-year-old man was diagnosed with gastric cancer in the middle stomach and intraductal papillary mucinous neoplasm of the pancreatic body. Radical cure surgery was performed using the da Vinci Xi robotic system. Conventional distal gastrectomy was initially completed using near-infrared ray guidance when transecting the stomach. After dividing the pancreas, the parenchyma of the distal pancreas was detached from the splenic artery and vein; multiple branches from these splenic vessels were dissected. Indocyanine green imaging confirmed sufficient blood flow in the splenic vessels and perfusion of the remnant stomach. Ultimately, gastrointestinal reconstruction was performed, and the postoperative course was uneventful. Conclusions The robotic distal gastrectomy plus spleen-preserving distal pancreatectomy procedure was safely performed. Compared to the total gastrectomy plus distal pancreatectomy with splenectomy procedure, this technique may improve the quality of dietary life, reduce weight loss, and prevent complications associated with splenectomy.